Social Behaviour of Humpback Whales (Megaptera novaeangliae) in Hervey Bay, Eastern Australia, a Preferential Female Stopover During the Southern Migration - Franklin, Trish; Franklin, Wally; Brooks, Lyndon; Harrison, Peter; Pack, Adam A.; Clapham, Phillip J. (Frontiers in Marine Science, 2021)
Agonistic competitive social behaviour in humpback whales (Megaptera novaeangliae (Borowski, 1781)) has been extensively studied and reported in previous research. However, non-agonistic social behaviour in humpback whale pods has not been systematically studied. We investigated the social behaviour of 3,949 humpback whale pods over a period of fourteen years during August, September and October in Hervey Bay (Queensland, Australia), a preferential female stopover early in the southern migration. Modeling and analyses of the data examined the factors influencing the occurrence and timing of non-agonistic social behaviour pods, agonistic competitive pods and newly associated pods. Non-agonistic social behaviour was observed more frequently during August when mature females, including early pregnant and resting females, co-occur and socially interact with immature males and females. Overall, relatively few mature males visit Hervey Bay. Agonistic competitive behaviour was observed with increasing frequency during September and October when mother-calf pods, with few escorts predominated. Mother-calf pods in Hervey Bay spent the majority of their time alone involved in maternal care. Agonistic competitive behaviour is related to the decreasing numbers of potentially estrous females towards the end of the season. Non-agonistic social behaviour and agonistic competitive behaviour were more frequently observed in larger and newly associated pods. Overall, non-agonistic social behaviour pods were more prevalent than agonistic competitive social behaviour pods. The results of this study substantiate that non-agonistic social behaviour may be more prevalent than aggressive agonistic social behaviour in site-specific locations and habitats, depending upon the classes and timings of humpback whales using such habitats.